Réponses

2014-10-15T20:56:28+02:00
Il faut développer et réduire
A = (3x - 1) (x + 8) - 6 (4x - 1) + x + 2
A = 3x² + 24x - x - 8 - 24x + 6 + x + 2
A = 3x²

Ensuite il faut calculer le plus simplement possible la valeur de A lorsque
a) x = (- 5)
A = 3x²
A = 3 * - 5²
A = 3 * 25
A = 75

b) x = 3.2

A = 3x²
A = 3 * 3,2²
A = 3 * 10,24
A = 30,72
2014-10-15T21:23:36+02:00
A= (3x-1) (x+8)-6 (4x-1) +x+2
  =3x*x+3x*8-1*x-1*8-6*4x-6*(-1)+x+2
  =3x²+24x-x-8-24x+6+x+2
  =3x²

a) x=-5
A=3x²
  =3*5²
  =3*25
  =75

b)x=3.2
A=3x²
  =3*3.2²
  =3*10.24
  =30.72

voilà ;)